Fundamentalisme dan Radikalisme Beragama Perspektif Agama dan Teori Sosial - Izzuddin, Naufal Azmi; Halimatussa’diyah, Halimatussa’diyah; Fadhliyah, Maulida Nur; Roibin, Roibin (LP2M IAIN kUDUS, 2024)
In the era of globalization, the discourse on religious fundamentalism and radicalism has become increasingly important and urgent. This research aims to understand the phenomena of religious fundamentalism and radicalism from both religious and social theory perspectives, as well as to identify their root causes and social impacts. The method used in this research is a literature study that examines various relevant sources and theories. The research findings indicate that religious fundamentalism is a movement that seeks to return to the fundamental teachings of religion and rejects changes toward modernism and secularism. From a religious perspective, fundamentalism is seen as an effort to preserve the purity of religious teachings, while from a social theory perspective, it is viewed as a reaction to social and political changes perceived as threatening to religious identity. Religious radicalism is defined as an extreme view or action in advocating for social and political change based on a radical interpretation of religious teachings. Social theory perspectives see radicalism as a response to social injustice, modernization, or globalization, which is often associated with violence and intolerance. This research concludes that while religious fundamentalism and radicalism share some similarities in their core religious principles, they have fundamental differences in their approaches and methods. The contribution of this research to the advancement of knowledge lies in providing a holistic analytical framework to understand the dynamics of fundamentalism and radicalism from religious and social perspectives. This study also offers deeper insights into the root causes and social impacts of these phenomena, which can serve as a foundation for developing more effective educational strategies and public policies in addressing religious extremism in the era of globalization.AbstrakDalam era globalisasi, diskursus mengenai fundamentalisme dan radikalisme beragama menjadi semakin penting dan mendesak. Penelitian ini bertujuan untuk memahami fenomena fundamentalisme dan radikalisme beragama dari perspektif agama dan teori sosial, serta mengidentifikasi akar penyebab dan dampak sosialnya. Metode yang digunakan dalam penelitian ini adalah studi literatur yang mengkaji berbagai sumber dan teori yang relevan. Hasil penelitian menunjukkan bahwa fundamentalisme agama adalah gerakan yang berusaha kembali ke ajaran dasar agama dan menolak perubahan menuju modernisme dan sekularisme. Perspektif agama memandang fundamentalisme sebagai upaya menjaga kemurnian ajaran agama, sementara perspektif teori sosial melihatnya sebagai reaksi terhadap perubahan sosial dan politik yang dianggap mengancam identitas agama. Radikalisme agama didefinisikan sebagai pandangan atau tindakan ekstrem dalam memperjuangkan perubahan sosial dan politik berdasarkan interpretasi radikal terhadap ajaran agama. Perspektif teori sosial memandang radikalisme sebagai respons terhadap ketidakadilan sosial, modernisasi, atau globalisasi, yang sering dikaitkan dengan kekerasan dan intoleransi. Penelitian ini menyimpulkan bahwa meskipun fundamentalisme dan radikalisme beragama memiliki beberapa kesamaan dalam prinsip dasar keagamaan, keduanya memiliki perbedaan mendasar dalam pendekatan dan metode yang digunakan. Kontribusi penelitian ini terhadap pengembangan ilmu pengetahuan terletak pada penyediaan kerangka analisis yang holistik untuk memahami dinamika fundamentalisme dan radikalisme dari perspektif agama dan sosial. Penelitian ini juga menawarkan wawasan yang lebih mendalam mengenai akar penyebab dan dampak sosial dari fenomena tersebut, yang dapat menjadi dasar bagi pengembangan strategi pendidikan dan kebijakan publik yang lebih efektif dalam menanggulangi ekstremisme beragama di era globalisasi.